2017
DOI: 10.1021/acsphotonics.7b00666
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Planar and Bulk Chirality Mixture in Plasmonic Λ-Shaped Nanostructures Caused by Symmetry Breaking Defects

Abstract: We report on the coexistence of planar and bulk chiral effects in plasmonic Λ-shaped nanostructure arrays arising from symmetry breaking defects. The manifestation of bi-(2D) and three-dimensional (3D) chiral effects are revealed by means of polarization tomography and confirmed by symmetry considerations of the experimental Jones matrix. Notably, investigating the antisymmetric and symmetric parts of the Jones matrix points out the contribution of 2D and 3D chirality in the polarization conversion induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…These peculiar features are most clearly described within the Jones formalism, starting in the circular basis of polarization | R ⟩, | L ⟩ with the Jones matrix of a birefringent (linear LB and circular CB) and dichroic (linear LD and circular CD) optical system (we define by J ̅ Jones matrices expressed in the basis of the circularly polarized states, and J Jones matrices written in the linear polarization basis): where for C = CB – i CD, L = LB – i LD measured along the linear | x ⟩, | y ⟩ polarization axes, and L ′ = LB′ – i LD′ along π/4-tilted (| x ⟩ ± | y ⟩)/√2 linear polarization axes. , The difference χ between diagonal elements of the Jones matrix is a measure of the optical activity of the system, with a real part proportional to circular dichroism (CD) and an imaginary part associated with circular birefringence (CB) according to For 2D chirality, reciprocity imposes J ll = J rr , that is, χ = 0, from the interconversion of the planar enantiomeric forms of the 2D chiral system when the propagation of the probing light beam is reversed. But, in the absence of any point symmetry, the square norm difference ρ = | J rl | 2 – | J lr | 2 of off-diagonal elements is nonzero and characterizes 2D chirality through what is known as the circular conversion dichroism (CCD): ,, that stems from the misalignment between LB and LD.…”
Section: Resultsmentioning
confidence: 99%
“…These peculiar features are most clearly described within the Jones formalism, starting in the circular basis of polarization | R ⟩, | L ⟩ with the Jones matrix of a birefringent (linear LB and circular CB) and dichroic (linear LD and circular CD) optical system (we define by J ̅ Jones matrices expressed in the basis of the circularly polarized states, and J Jones matrices written in the linear polarization basis): where for C = CB – i CD, L = LB – i LD measured along the linear | x ⟩, | y ⟩ polarization axes, and L ′ = LB′ – i LD′ along π/4-tilted (| x ⟩ ± | y ⟩)/√2 linear polarization axes. , The difference χ between diagonal elements of the Jones matrix is a measure of the optical activity of the system, with a real part proportional to circular dichroism (CD) and an imaginary part associated with circular birefringence (CB) according to For 2D chirality, reciprocity imposes J ll = J rr , that is, χ = 0, from the interconversion of the planar enantiomeric forms of the 2D chiral system when the propagation of the probing light beam is reversed. But, in the absence of any point symmetry, the square norm difference ρ = | J rl | 2 – | J lr | 2 of off-diagonal elements is nonzero and characterizes 2D chirality through what is known as the circular conversion dichroism (CCD): ,, that stems from the misalignment between LB and LD.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted however that discrepancies are detected, especially between the linearly polarized side beams: while the theoretical data predict linear states aligned along X and Y , we experimentally observe slight ellipticity and rotation of the linear axis in Figure b,d,f,h. In addition to experimental errors coming from misaligments and the polarizers, it has been reported that subbtle imperfections in the shape of the nanostructures due to fabrication errors can lead to optical activity and dichroism as a result of break of symmetry in the system. Source of deviations could then arise from structural defects in the sample. Nevertheless, the conversion of SP with opposite trajectories into free-space radiation of opposite helicity with high DCP strongly confirms the reverse SHEL coupling occurring in our plasmonic system.…”
mentioning
confidence: 99%
“…The third field of application for symmetry breaking is chiral plasmonics. A couple of groups reported on chiral plasmonic nanostructures with symmetry breaking (see Table 3) such as Au nanorod equilateral trimers [83], chiral metamaterials composed of plasmonic slanted nanoapertures [84], plasmonic Λ-shaped nanostructures [85], plasmonic ramp-shaped nanostructures [86], 3D plasmonic crescents [87], and GaAS/Au nanowires [88].…”
Section: Applications To Chiral Plasmonicsmentioning
confidence: 99%
“…Improved Performances Applications [83] Hybridized plasmon modes Optical magnetic field enhancement [84] Circular dichroism in transmission Chiral imaging, sensing, and spectroscopy [85] 3D chiral effects Study of complex plasmonic nanostructures [86] Circular dichroism Nanoscale circular polarizers [87] Tailoring of circular dichroism Chiral sensing and circular dichroism spectroscopy [88] Circular dichroism Chiral sensing devices…”
Section: Refsmentioning
confidence: 99%